2009
DOI: 10.1113/jphysiol.2009.176289
|View full text |Cite
|
Sign up to set email alerts
|

Maternal prolactin inhibition during lactation programs for metabolic syndrome in adult progeny

Abstract: Neonatal malnutrition is associated with metabolic syndrome in adulthood. Maternal hypoprolactinaemia at the end of lactation (a precocious weaning model) caused obesity, leptin resistance and hypothyroidism in adult offspring, suggesting an association of prolactin (PRL) and programming of metabolic dysfunctions. Metabolic syndrome pathogenesis is still unclear, but abdominal obesity, higher triglycerides, lower high-density lipoprotein (HDL-c) and insulin resistance have been proposed to be important factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 69 publications
6
58
1
1
Order By: Relevance
“…Our results show that the Bro-Sed offspring had symptoms of metabolic syndrome, including visceral obesity, hypertriglyceridemia, lower HDL-c, hypertension, and insulin resistance, as similar results previously reported by our laboratory (Bonomo et al 2007, Moura et al 2009). Physical training consisting of low-intensity short-duration chronic exercise on motorized running wheels induced higher fitness levels in regular rats (C-Ex group).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results show that the Bro-Sed offspring had symptoms of metabolic syndrome, including visceral obesity, hypertriglyceridemia, lower HDL-c, hypertension, and insulin resistance, as similar results previously reported by our laboratory (Bonomo et al 2007, Moura et al 2009). Physical training consisting of low-intensity short-duration chronic exercise on motorized running wheels induced higher fitness levels in regular rats (C-Ex group).…”
Section: Discussionsupporting
confidence: 92%
“…In the first model, we used a pharmacological approach to inhibit the production of maternal prolactin (PRL) with the dopamine agonist bromoa-ergocryptine (Bro). This method programs for obesity, hyperleptinemia, leptin resistance (Bonomo et al 2007), and hypothyroidism (Bonomo et al 2008), and symptoms (including insulin resistance and an altered lipid profile) are similar to those of metabolic syndrome (Moura et al 2009). More recently, we obtained a similar profile in adult animals with a non-pharmacological model where a maternal bandage was used to cover the teats of the dam in the late lactation, thus also inducing an early weaning of offspring (Lima et al 2011(Lima et al , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…In studies with experimental animal models, Moura et al (2009) caused early weaning by applying a compound that prevents the production of prolactin, the hormone that induces the secretion of milk, to the female rat. The animals that weaned earlier reached adulthood with 10% more weight, 40% more total fat and up to 300% more visceral fat (that formed within the organs and hence the most harmful).…”
Section: Importance Of Breastfeedingmentioning
confidence: 99%
“…As expected, the rodents in the first group ate less, but those in the second group continued feeding, which indicated they showed no response to the hormone. Moura et al (2009) observed another hormonal imbalance: rats weaned prematurely developed hypothyroidism. They presented 50% lower blood levels of the hormone thyrotropin, whose function is to activate the thyroid gland, which produces Braz.…”
Section: Importance Of Breastfeedingmentioning
confidence: 99%
See 1 more Smart Citation